100 years of thiosemicarbazone: a bibliometric study using Scopus database - M. Osman, Uwaisulqarni; W. M. Kharul Anwar, W. M. Zulhilmi; Mohd Ghazali, Mohd Sabri; Razali, Mohd Hasmizam; Rozaini, Mohd Zul Helmi; Juahir, Yusnita; Ismail, Mohamad Wafiuddin; Wan Ismail, Wan Izhan Nawawi (Malaysian Analytical Sciences Society (ANALIS), 2025)
Thiosemicarbazones (TSC) have received much attention in the scientific community due to their potential therapeutic applications, particularly in cancer and infectious disease treatment. This study aims to provide a comprehensive analysis of the global research trends, key contributors, and collaboration networks in TSC research. The bibliometric analysis utilizes a refined dataset of 6287 articles sourced from the Scopus database, covering the extensive period from 1922 to 2022. Based on the collected data, it can be determined that significant growth has occurred for the past century in TSC-related publications, especially in recent decades, with India, China, and the United States have emerged as major contributors to a substantial portion of the research output. In brief, this study provides valuable insights into global research dynamics, highlighting major contributors and emerging trends. Three most emerging trends discovered by this analysis are shift toward multifunctional therapeutic applications; development of metal complexes for enhanced bioactivity and globalization of research with growing contributions and collaborations. The implications of these findings underscore the importance of strategic partnerships and interdisciplinary approaches in propelling TSC research forward in the coming years. This study provides the first comprehensive, century-long analysis of global research trends on thiosemicarbazone (TSC), revealing its growing importance in therapeutic applications such as cancer and antimicrobial treatment. It identifies key contributors, emerging topics, and international collaborations, offering a valuable roadmap for future research. By visualizing data through bibliometric tools, the study supports evidence based decision making for researchers and institutions.